The Legal-Political Paradox in Granting Absolute Jurisdiction to the Administrative Court (PTUN) over the Judicial Review of Abuse of Authority in Indonesia - Ardiansyah, Nike; Nur, Muhammad; Haeril, Haeril (JURNAL SYNTAX IMPERATIF : Jurnal Ilmu Sosial dan Pendidikan, 2025)
This study examines the legal-political paradox behind granting the Administrative Court (PTUN) authority to assess abuse of power by public officials, and how it affects criminal law enforcement. Using a qualitative socio-legal method, data were collected through legal document analysis, interviews with judges, scholars, and practitioners, and court ruling reviews. While the Administrative Law grants PTUN binding authority, its scope is limited by Supreme Court Regulation No. 4 of 2015 (Perma 4/2015), particularly due to the vague phrase “after APIP oversight.” According to the Supreme Court, only 12 abuse-of-power (PW) cases were filed between 2015 and 2022—most rejected on procedural grounds. Of the three cases ruled without abuse found, two were still prosecuted criminally. This reveals the court’s weak role in protecting officials’ discretionary authority. The study concludes that institutional and regulatory flaws blur the line between administrative and criminal law, undermining PTUN’s corrective function. A comprehensive revision of Perma 4/2015 and institutional strengthening of PTUN are urgently needed to ensure a legal framework that is fair, rational, and accountable for public officials operating within the bounds of lawful administrative discretion.